Factors Affecting Financial Statement Quality: Analysis of Cloud Accounting, Digital Literacy, and Management Support Mediated by Digital Competence - Sri Rusiyati (Greenation International Journal of Economics and Accounting, 2025)
The purpose of this study is to develop hypotheses related to factors that influence the quality of financial reports, especially in the SME sector in Jabodetabek. The writing technique used in this literature review is comparative analysis. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach were obtained from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this literature review are as follows: 1) Cloud accounting influences digital competence; 2) Digital literacy influences digital competence; 3) Management support influences digital competence; 4) Cloud accounting influences the quality of financial statements; 5) Digital literacy influences the quality of financial statements; 6) Management support influences the quality of financial statements; 7) Digital competence influences financial report quality; 8) Cloud accounting influences financial report quality through digital competence; 9) Digital literacy influences financial report quality through digital competence. This study is limited to financial report quality in SMEs in Jabodetabek; and 10) Management support influences financial report quality through digital competence. This study contributes to the understanding of factors influencing financial report quality, with a focus on factors such as cloud accounting, digital literacy, management support, and digital competence. This research provides new insights into other factors influencing financial report quality, particularly in SMEs in Jabodetabek. Thus, it can serve as a reference for future literature.